Attitudes and Views of Universitas Ahmad Dahlan to the Transable Ideology: An AIK Learning and Local Wisdom Based Preventive Approach - Aabidah Ummu 'Azizah; Sukiman Sukiman; Sibawaih Sibawaih; Unik Hanifah Salsabila (Universitas Muhammadiyah Malang, 2024)
This research explores the views of Universitas Ahmad Dahlan (UAD) towards transabled individuals and UAD's role in rejecting transabled individuals. Transabled refers to individuals who desire physical disability or engage in self-destructive behavior. This research focuses on the role of Islamic education through Al-Islam and Muhammadiyah (AIK) learning at UAD in forming attitudes towards the transabled. The research method uses a qualitative approach with in-depth interviews as a data collection technique and Paulo Freire’s critical education theory as a data analysis technique. Research respondents comprised students, lecturers, and administrative staff in the Public Health Sciences (IKM) study program, Faculty of Public Health (FKM) UAD. The research results show that IKM FKM UAD has an active role in rejecting the transabled concept. The role can be seen through the problem-solving approach to AIK learning in the IKM FKM UAD study program, which provides an understanding of physical disabilities within Islamic values and teaches the importance of accepting the body as God's creation with gratitude. Apart from that, AIK learning also builds a gratitude paradigm by creating an environment that utilizes individual well-being for both students who do not have physical limitations and those with disabilities. Local wisdom also plays a role in preventing transability with the values ​​of civility and social righteousness. AIK learning also encourages discussion about ethical considerations surrounding body integrity and self-identity. This perspective allows students to consider the social, psychological, and ethical impacts of changing God’s creation or engaging in intentionally destructive behavior.